The Myth That Only Brilliant People Are Good at Math and Its Implications for Diversity - Eleanor K. Chestnut; Ryan F. Lei; Sarah-Jane Leslie; Andrei Cimpian (MDPI AG, 2018)
A common misconception about math is that it requires raw intellectual talent or “brilliance.” Only students who possess this sort of brilliance are assumed to be capable of success in math-related subjects. This harmful myth has far-reaching consequences for the success of girls and children from ethnic-minority backgrounds in these subjects. Because women and minorities are stereotyped as lacking brilliance, the myth that success in math requires this trait is a barrier that students from these groups have to overcome. In the first part of this paper, we detail the pervasiveness of this myth and explore its relation to gender and race gaps in math and beyond. In the second part, we highlight some potential sources of this myth in children’s everyday experiences and offer some strategies for debunking it.